Assembling Two‐Phase Enzymatic Cascade Pathways in Pickering Emulsion. Issue 7 (7th April 2019) - Pan, Yongchun; Qiu, Wu; Li, Qin; Zhu, Shuihong; Lin, Changxu; Zeng, Wenbin; Xiong, Xueqing; Liu, Xiang Yang; Lin, Youhui
Abstract: The front cover artwork for Issue 07/2019 is provided by researchers from Xiamen University (China) and National University of Singapore (Singapore). The image shows a one‐pot biphasic enzymatic cascade pathway with the aid of Pickering emulsion. See the Communication itself athttps://doi.org/10.1002/cctc.201900098 . Abstract : " How do enzymes remain active and stable? " This and more about the story behind the research featured on the front cover can be found in this issue's Cover Profile. Read the full text of the corresponding research athttps://doi.org/10.1002/cctc.201900098 .